Forming method and application of silica fume particles
Through the processes of ore distribution, pressing, drying and high-temperature consolidation, microsilicon powder particles with high mechanical strength and thermal stability were prepared, which solved the problems of waste of microsilicon powder resources and environmental pollution, and achieved effective utilization of resources and reduced production costs.
Patent Information
- Application Number
- CN202311406504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2025-04-29
AI Technical Summary
Due to the fine particle size, microsilicon powder cannot be effectively utilized, resulting in waste of valuable resources and environmental pollution, and at the same time increases production costs.
Through the steps of ore distribution, pressing, drying and high temperature consolidation, microsilicon powder particles with good mechanical strength and thermal stability were prepared and returned to the reduction furnace.
It improves the mechanical strength and thermal stability of micro-silica powder particles, reduces secondary dust output, reduces production costs, and saves resources.
Smart Images

Figure CN119899024A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the field of silicon smelting, and in particular to a forming method of micro silicon powder particles and application thereof. Background technology:
[0002] During the silica smelting process, due to its poor thermal stability and the reduction and volatilization of SiO, a large amount of fine silica dust (referred to as microsilica powder) is produced. Its output rate is estimated to be as high as about 30%. 2 However, due to the fine particle size of microsilica powder, after it is directly recycled into the reduction furnace, it can only stay on the furnace surface for a short time and then be carried away by the flue gas, which not only fails to recycle SiO 2 Therefore, enterprises usually collect dust through dust removal equipment and sell it at a low price for use in industries such as concrete and cement.
[0003] The microsilica powder has a fine particle size and is mainly spherical. The average particle size is d = 15.59 μm and the specific surface area is 1286 m 2 / kg, some particles are nanometer-sized and have low density, which makes them unsuitable for molding using conventional pelletizing technology.
[0004] Therefore, at present, microsilica powder cannot be effectively utilized due to its fine particle size, and there is currently no mature molding process. It can usually only be sold at a low price or stockpiled, which not only causes a large amount of waste of precious resources and brings environmental pollution, but also leads to a significant increase in production costs. Summary of the invention:
[0005] In order to solve the above problems, the first object of the present invention is to provide a method for forming microsilica powder particles. The second object of the present invention is to provide an application of microsilica powder particles.
[0006] The first object of the present invention is implemented by the following technical solutions:
[0007] A method for forming microsilica powder particles comprises the following steps:
[0008] S1. Mineral preparation: Mix the microsilica powder and the binder in proportion, and add a certain amount of water to control the molding moisture content at 15-30% to obtain a premix;
[0009] S2, briquetting: briquetting the premix obtained in S1, ore blending, to obtain raw briquettes with a diameter of 70 mm and a thickness of 40±5 mm;
[0010] S3, drying: subjecting the raw agglomerates obtained in S2, agglomeration, to dynamic drying to obtain dry agglomerates;
[0011] S4, consolidation: the dry agglomerates obtained in S3, drying, are preheated and consolidated to obtain preheated agglomerates, i.e., microsilica powder particles.
[0012] Furthermore, in the S1, ore blending, the binder is industrial starch.
[0013] Furthermore, in the S1, the weight ratio of microsilica powder to binder is 100:(2-5).
[0014] Furthermore, in the S2, pressing the pellets, the molding pressure is 15 to 20 MPa.
[0015] Furthermore, in the drying step S3, forced air drying is first performed, and then exhaust air drying is performed, wherein the forced air drying has a temperature of 280-320°C, a time of 10-20 min, and a wind speed of 1.3-1.7 m / s; the exhaust air drying has a temperature of 320-370°C, a time of 25-35 min, and a wind speed of 1.2-1.6 m / s.
[0016] The green pellets obtained by pressing are dried to heat the green pellets to remove moisture. Blast drying refers to the process in which hot air passes through the material layer from bottom to top to remove moisture from the green pellets. Exhaust drying refers to the process in which hot air passes through the material layer from top to bottom to remove moisture from the green pellets.
[0017] The purpose of forced air drying is to dry the green pellets below, and the purpose of exhaust air drying is to prevent the upward water vapor caused by forced air drying from condensing through the upper material layer. Therefore, forced air drying is performed first and then exhaust air drying to ensure that the green pellets at the height of the entire material layer can be dried thoroughly. Otherwise, the residual moisture in the microsilica powder agglomerates will be too high, causing bursting in the subsequent preheating stage.
[0018] Furthermore, in the S4 consolidation, a transition stage is first passed, and then a preheating stage is passed, wherein the temperature of the transition stage is 600-700°C, the time is 3-7 minutes, and the wind speed is 1.5-3.0 m / s; the temperature of the preheating stage is 850-950°C, the time is 10-30 minutes, and the wind speed is 2.0-2.8 m / s.
[0019] Dividing the consolidation into two stages can prevent the microsilica powder agglomerates from bursting due to excessive vapor pressure inside the agglomerates caused by rapid temperature rise.
[0020] The second object of the present invention is implemented by the following technical solutions:
[0021] An application of microsilica powder particles. After the microsilica powder particles are naturally cooled, the microsilica powder particles, silica and a reducing agent are added into a reduction furnace in proportion to participate in a reduction reaction.
[0022] Furthermore, the weight ratio of the microsilica powder particles to silica and the reducing agent is 1:(0.7-1):(0.64-0.65).
[0023] Advantages of the present invention:
[0024] 1. After the microsilica powder is pressed, dried and solidified at high temperature, SiO 2 The grains grow by solid phase diffusion and a small amount of liquid phase to form thicker connecting necks or connecting bridges, so that the consolidation of the agglomerates is improved. Therefore, the microsilica powder particles obtained by the present invention have good mechanical strength and thermal stability.
[0025] 2. High temperature consolidation can improve the strength of microsilica powder particles, while also helping to reduce the amount of binder used and reduce production costs.
[0026] 3. The present invention can significantly reduce the output of secondary dust, lower production costs and save resources by making microsilica powder into microsilica powder particles with high thermal stability and high mechanical strength and then reusing them in the reduction furnace.
[0027] 4. The adhesive component involved in the present invention is single, which is only industrial starch, which reduces the types of adhesives, reduces the cost of adhesives, and reduces the processing cost of enterprises. Description of the drawings:
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0029] Figure 1 This is a macroscopic image of the microsilica powder particles of Example 1 after anti-burst index test;
[0030] Figure 2 This is a macroscopic image of the microsilica powder particles of Comparative Example 2 after anti-burst index test;
[0031] Figure 3 This is a macroscopic image of the microsilica powder particles of Example 2;
[0032] Figure 4 This is a macroscopic image of the microsilica powder particles of Comparative Example 3;
[0033] Figure 5 This is a macroscopic image of the microsilica powder particles of Comparative Example 4;
[0034] Figure 6 This is a macroscopic image of the microsilica powder particles of Comparative Example 5; Specific implementation method:
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Embodiment 1:
[0037] A method for forming microsilica powder particles comprises the following steps:
[0038] S1. Mineral preparation: Mix microsilica powder, industrial starch and water in a weight ratio of 100:5, and add a certain amount of water to control the molding moisture content at 17% to obtain a premix;
[0039] S2. briquetting: The premix obtained in S1. ore blending is briquetting to obtain green briquettes with a diameter of 70 mm and a thickness of 40±5 mm; wherein the molding pressure is 20 MPa.
[0040] S3, drying: subjecting the raw mass obtained in S2, agglomeration, to dynamic drying to obtain dry mass;
[0041] Dynamic drying is first performed by blast drying and then by exhaust drying, wherein the temperature of blast drying is 280°C, the time is 10 minutes, and the wind speed is 1.3 m / s; the temperature of exhaust drying is 320°C, the time is 25 minutes, and the wind speed is 1.2 m / s.
[0042] S4, consolidation: preheating and consolidating the dry mass obtained in S3, drying to obtain preheated mass, i.e., microsilica powder particles;
[0043] The preheating consolidation is first a transition stage and then a preheating stage, wherein the temperature of the transition stage is 600°C, the time is 3 minutes, and the wind speed is 1.5 m / s; the temperature of the preheating stage is 850°C, the time is 10 minutes, and the wind speed is 2.0 m / s.
[0044] Embodiment 2:
[0045] A method for forming microsilica powder particles comprises the following steps:
[0046] S1. Mineral preparation: Mix microsilica powder, industrial starch and water in a weight ratio of 100:2, and add a certain amount of water to control the molding moisture content at 17% to obtain a premix;
[0047] S2. briquetting: The premix obtained in S1. ore blending is briquetting to obtain green briquettes with a diameter of 70 mm and a thickness of 40±5 mm; wherein the molding pressure is 20 MPa.
[0048] S3, drying: subjecting the raw mass obtained in S2, agglomeration, to dynamic drying to obtain dry mass;
[0049] Dynamic drying is carried out in two stages: forced air drying and then exhaust air drying. The forced air drying temperature is 300°C, the time is 15 minutes, and the wind speed is 1.4 m / s; the exhaust air drying temperature is 350°C, the time is 30 minutes, and the wind speed is 1.4 m / s.
[0050] S4, consolidation: preheating and consolidating the dry mass obtained in S3, drying to obtain preheated mass, i.e., microsilica powder particles;
[0051] The preheating consolidation first goes through a transition stage and then a preheating stage. The temperature of the transition stage is 650°C, the time is 5 minutes, and the wind speed is 2.4 m / s; the temperature of the preheating stage is 900°C, the time is 20 minutes, and the wind speed is 2.4 m / s.
[0052] Embodiment 3:
[0053] A method for forming microsilica powder particles comprises the following steps:
[0054] S1. Mineral preparation: Mix microsilica powder, industrial starch and water in a weight ratio of 100:2, and add a certain amount of water to control the molding moisture content at 17% to obtain a premix;
[0055] S2. briquetting: The premix obtained in S1. ore blending is briquetting to obtain green briquettes with a diameter of 70 mm and a thickness of 40±5 mm; wherein the molding pressure is 20 MPa.
[0056] S3, drying: subjecting the raw mass obtained in S2, agglomeration, to dynamic drying to obtain dry mass;
[0057] Dynamic drying is carried out in two stages: forced air drying and exhaust air drying. The forced air drying temperature is 320°C, the time is 20 minutes, and the wind speed is 1.7 m / s; the exhaust air drying temperature is 370°C, the time is 35 minutes, and the wind speed is 1.6 m / s.
[0058] S4, consolidation: preheating and consolidating the dry mass obtained in S3, drying to obtain preheated mass, i.e., microsilica powder particles;
[0059] The preheating consolidation first goes through a transition stage and then a preheating stage. The temperature of the transition stage is 700°C, the time is 7 minutes, and the wind speed is 2.9 m / s; the temperature of the preheating stage is 950°C, the time is 30 minutes, and the wind speed is 2.8 m / s.
[0060] Embodiment 4:
[0061] An application of microsilica powder particles. After the microsilica powder particles prepared in Example 1 are naturally cooled to 150° C., the microsilica powder particles, silica and a reducing agent are added into a reduction furnace at a weight ratio of 1:1:0.65 to participate in a reduction reaction, thereby realizing the recycling of the microsilica powder.
[0062] Comparative Example 1:
[0063] The difference between this comparative example and Example 1 is that the step S4, consolidation, is eliminated, that is, the dry agglomerates are used as the final microsilica powder particles.
[0064] Since the organic matter of microsilica powder particles will decompose at about 300℃, which will have an adverse effect on the structure and strength of the agglomerate, the thermal stability is poor, and the microsilica powder particles are difficult to withstand the thermal shock after entering the submerged arc furnace, causing the structure and strength to deteriorate. This means that after the dry agglomerate enters the submerged arc furnace, it is very easy to thermally explode, and it may also be crushed and pulverized by other materials, affecting the permeability of the charge. Only relying on pressed and dried microsilica powder particles cannot meet the smelting requirements of the submerged arc furnace.
[0065] Comparative Example 2:
[0066] The only difference between this comparative example and Example 2 is that during S4, the consolidation process, the temperature of the preheating stage is 800°C.
[0067] Comparative Example 3:
[0068] The difference between this comparative example and Example 2 is that during S4, the consolidation process, the temperature of the preheating stage is 1000°C.
[0069] Comparative Example 4:
[0070] The difference between this comparative example and Example 2 is that in S4, the consolidation process, the preheating stage time is 7 minutes.
[0071] Comparative Example 5:
[0072] The difference between this comparative example and Example 2 is that in S4, the consolidation process, the preheating stage time is 45 minutes.
[0073] In order to compare the performance of the microsilica powder particles obtained in Implementation 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5, the performance parameters of the 8 types of microsilica powder particles obtained above were measured, and the results are shown in Table 1.
[0074] Among them, the anti-burst index refers to putting microsilica powder particles into an anti-burst index test container, gradually raising the temperature from room temperature to 1300°C and maintaining it for 15 minutes, then taking the microsilica powder particles out of the anti-burst index test container and measuring the percentage of the weight of particles with a particle size greater than 20mm in the total weight to simulate the anti-explosion performance of microsilica powder particles in the high temperature environment of a reduction furnace.
[0075] Table 1 Performance parameters of microsilica powder particles obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4, 5
[0076]
[0077] Note: In the table, / indicates no relevant data were detected.
[0078] According to the data in the above table, it can be seen from the compressive strength, AC drum strength and burst resistance index of Example 1 and Comparative Example 1 that the compressive strength and AC drum strength of Comparative Example 1 cannot meet the requirements of smelting in an electric arc furnace because it has not been preheated and consolidated. Figure 1 and Figure 2 It can be clearly seen that after being subjected to a high temperature of 1300°C, the microsilica powder particles of Example 1 can maintain their original morphology, without cracking or fragmentation, while the dry agglomerate structure of Comparative Example 1 is significantly damaged, with large cracks or fragmentation. This means that after the dry agglomerate enters the electric arc furnace, it is very easy to explode, and it may also be crushed and pulverized by other materials, affecting the chemical reactions during the smelting process.
[0079] It can be seen from the data of Examples 1 and 3 that by increasing the preheating and consolidation temperature, the amount of binder can be reduced, and the performance of the microsilica powder particles will not decrease, but the higher the preheating and consolidation temperature is not necessarily better.
[0080] It can be seen from the compressive strength of Example 2 and Comparative Example 2 that the compressive strength of the microsilica powder particles obtained in Comparative Example 2 is much lower than that of the microsilica powder particles obtained in Example 2. Therefore, in the consolidation process, the compressive strength of the microsilica powder particles will be seriously affected if the temperature in the preheating stage is too low. At the same time, it can be seen from Comparative Example 3 that if the preheating temperature is too high, the compressive strength of the microsilica powder particles will be improved, but if the temperature is too high, microcracks will appear on the surface of the microsilica powder particles, such as Figure 4 As shown in Figure 2, the particle integrity rate will decrease significantly; however, Figure 3 It can be seen that the microsilica powder particles of Example 2 do not produce cracks and the macroscopic appearance remains intact.
[0081] Similarly, it can be seen from the experimental data of Comparative Examples 4 and 5 that if the preheating time is too short or too long, the compressive strength of the microsilica powder particles will be lower than the compressive strength of the present invention. Figure 5 and Figure 6 It can be seen that if the preheating stage is too long, it will seriously affect the integrity of the particles, and the microsilica particles will have cracks, which will affect their strength.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for forming microsilica powder particles, characterized in that: The following steps are involved: S1. Mineral preparation: Mix the microsilica powder and the binder in proportion, and add a certain amount of water to control the molding moisture content at 15-30% to obtain a premix; S2, briquetting: briquetting the premix obtained in S1, ore blending, to obtain raw briquettes with a diameter of 70 mm and a thickness of 40±5 mm; S3, drying: subjecting the raw agglomerates obtained in S2, agglomeration, to dynamic drying to obtain dry agglomerates; S4, consolidation: the dry agglomerates obtained in S3, drying, are preheated and consolidated to obtain preheated agglomerates, i.e., microsilica powder particles.
2. The method for forming microsilica powder particles according to claim 1, characterized in that: In the above-mentioned S1, in the ore preparation, the binder is industrial starch.
3. The method for forming microsilica powder particles according to claim 1, characterized in that: In the S1, the weight ratio of microsilica powder to binder is 100:(2-5).
4. The method for forming microsilica powder particles according to claim 1, characterized in that: In the step S2, during the briquetting, the molding pressure is 15-20 MPa.
5. The method for forming microsilica powder particles according to claim 1, characterized in that: In the drying step S3, air blast drying is first performed, and then air exhaust drying is performed, wherein: The temperature of blast drying is 280-320℃, the time is 10-20min, and the wind speed is 1.3-1.7m / s; The temperature of exhaust drying is 320-370°C, the time is 25-35 minutes, and the wind speed is 1.2-1.6 m / s.
6. The method for forming microsilica powder particles according to claim 1, characterized in that: In the S4, consolidation, first a transition stage is passed, then a preheating stage is passed, wherein: The temperature in the transition stage is 600-700°C, the time is 3-7 minutes, and the wind speed is 1.5-3.0 m / s; The temperature in the preheating stage is 850-950°C, the time is 10-30 minutes, and the wind speed is 2.0-2.8 m / s.
7. The use of microsilica powder particles obtained by the molding method of microsilica powder particles according to any one of claims 1 to 6, characterized in that: After the microsilica powder particles are naturally cooled, the microsilica powder particles, silica and a reducing agent are added into a reduction furnace in proportion to participate in the reduction reaction.
8. The use of microsilica powder particles according to claim 7, characterized in that: The weight ratio of microsilica powder particles to silica and reducing agent is 1:(0.7-1):(0.64-0.65).
Citation Information
Patent Citations
Method for preparing metallurgy aggregates by metal silicon fine powder
CN101884895A
Ore fine agglomerate to be used in sintering process and production process of ore fines agglomerate
CN102666886A
Method for producing ferrosilicon alloy by use of silica fume
CN103602846A
Forming method for improving production efficiency of vanadium-titanium pellets and iron concentration machining method
CN108754135A
Process for producing silicon metal-containing agglomerates
CN112384474A